Artificial neural network-fast evolutionary programming (FEP) technique for lightning prediction / Roymelvin Ricky - Ricky, Roymelvin (2009)
Lightning is a natural phenomenon that is common all over the world. The occurence of these phenomena is renowned for its effect. Over the years, various lightning prediction system have been developed to predict lightning.